رحلة بلدوين البولوني من الرها لاعتلاء عرش بيت المقدس "2 أكتوبر - 9 نوفمبر 1100 م. / 27 ذي القعدة 493 هـ. - 4 محرم 494 هـ." - بنيرة، هويدا محمد أحمد (جامعة بني سويف - كلية الآداب, 2022)
أثارت وفاة جودفري في ١٨ يوليو ١١٠٠ م /٩ رمضان 493 ه مسألة هامة وخطيرة بالنسبة للصليبيين في بيت المقدس إلا وهي اختيار خليفة لجودفري مما أدي إلى حدوث فراغ سياسي ونشوب الصراع على هذا المنصب بين فريقين أو حزبين قويين في المدينة المقدسة الحزب الأول تزعمه دايمبرت بطريرك بيت المقدس صاحب الطموح السياسي والذي كان يأمل في أن يخلف جودفري في حكم بيت المقدس وانضم إليه تنكريد ابن أخت بوهيمند أما الحزب الثاني فقد ضم فرسان بيت المقدس من اللوثارنجيين الذين رفضوا فكرة قيام حكومة ثيوقراطية وتسليم الحكم إلي البطريرك دايمبرت البيزى الذي قرر بالإتفاق مع تنكريد ضرورة استدعاء بوهيمند لمساعدته في إعتلاء عرش بيت المقدس ولكن خابت آمال الرجلين دايمبرت وتنكريد بسبب عدم وصول الرسالة إلي بوهيمند الذي وقع في الأسر في بداية أغسطس ١١٠٢ م / رمضان 493 ه وهو يجهل تماما أحداث بيت المقدس أما الحزب الآخر المناؤى فقد أرسل مبعوثين من قبله إلي الرها لمقابلة بلدوين واستدعائه ليخلف أخاه جودفري في حكم بيت المقدس واستقبل بلدوين مبعوثي المدينة المقدسة واستجاب لطلبهم وبدأ رحلته إلي الرها في ٢ أكتوبر ١١٠٠م/٢٧ ذي القعدة ٤٩٣ ه بمحاذاة ساحل البحر المتوسط فوصل إلي أنطاكية ومنها إلي اللاذقية ثم إلي طرابلس حيث أرسل له الأمير فخر الملك بن عمار المؤن والزاد وبالقرب من بيروت نصب له دقاق أمير دمشق وجناح الدولة حسين صاحب حمص وعضد الدولة التنوخي زعيم الدروز في جبل لبنان كمينا لاصطياده ومنعه من استكمال رحلته والوصول إلي بيت المقدس وعند مصب نهر الكلب دارت معركة خطيرة بين الجانبين استمرت يومين ٢٤ -٢٦ أكتوبر ١١٠٠ م/ ٢٣ - ٢٥ ذي الحجة 493 ه انتهت بانتصار بلدوين الذي واصل سيره عبر الطريق الساحلي حتي وصل إلي بيت المقدس في ٩ نوفمبر ١١٠٠م/ ٤ محرم ٤٩٣ه ليتم تتويجه بعد ذلك كأول ملك لبيت المقدس في ٢٤ ديسمبر ١١٠٠ م/ ١٥ صفر ٤٩٤ه. Godfrey’s death on July 18,1100 CE/Ramadan 9,493 AH raised an important and dangerous issue for the Crusaders in Jerusalem, namely the selection of a successor to Godfrey, which led to a political vacuum and the outbreak of conflict over this position between two strong parties or parties in the Holy City. The first party was led by Dimbert, the ambitious Patriarch of Jerusalem. The politician, who had hoped to succeed Godfrey in the rule of Jerusalem, was joined by Bohemand's nephew Tancred. The second party included the Lutherans, the Knights of Jerusalem, who rejected the idea of ,establishing a theocratic government and handing over power to Dimbert who decided, in agreement with Tencred, that Bohemand should be summoned to help him ascend the throne of the House. Al-Maqdis, but the hopes of the two men, Dimbert and Tancred, were disappointed because the message did not reach Bohemand, who was captured at the beginning of August 1102AD / Ramadan 493 AH and is completely ignorant of the events of Jerusalem. Baldwin received the envoys of the Holy City and responded to their request and began his journey to Edessa on October 2.1100 AD /27 Dhu al-Qa’dah 493 AH, along the Mediterranean coast. Takia and from there to Lattakia and then to Tripoli, where Prince Fakhr al-Malik bin Ammar sent him supplies and provisions. Near Beirut, the Duqaq of the Emir of Damascus and the State Pavilion, Hussein, the owner of Homs, and the Add al-Dawla al-Tanukhi, the leader of the Druze in Mount Lebanon, set an ambush to hunt him and prevent him from completing his journey and reaching Jerusalem and at the mouth of the Nahr al-Kalb A serious battle took place between the two sides that lasted for two days from October 24-26AD / 23-25 Dhu al Hijjah 493 AH, which ended with the victory of Baldwin, who continued his ,march along the coastal road until he reached Jerusalem on November 9 AD / Muharram 493 AH, to be crowned after that as the first king Bait 1100 Al-Maqdis on December 24,1100 CE / Safar 15,494 AH
Keywords: التاريخ القديم -- بلدوين البولوني -- الطموح السياسي -- معركة نهر الكلب -- الحروب الصليبية